2020
DOI: 10.1155/2020/6261748
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa: An Uncommon Cause of Antibiotic-Associated Diarrhea in an Immunocompetent Ambulatory Adult

Abstract: Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen known to cause enterocolitis in children, amongst other types of infections. Pseudomonas aeruginosa has been widely reported as a cause of antibiotic-associated diarrhea in adult immunocompromised hosts. We present an 81-year-old previously healthy female as the first reported case of Pseudomonas aeruginosa antibiotic-associated diarrhea in an immunocompetent host in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In addition, the study isolated Shigella spp. (7.5%) and P. aeruginosa (0.3%), bacteria associated with severe gastrointestinal infections such as chronic diarrhea and enterocolitis [ 30 ]; [ 31 ]. A similar study by Wardhana et al (2021) [ 32 ] also reported a high prevalence of S. aureus (58.3%), Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study isolated Shigella spp. (7.5%) and P. aeruginosa (0.3%), bacteria associated with severe gastrointestinal infections such as chronic diarrhea and enterocolitis [ 30 ]; [ 31 ]. A similar study by Wardhana et al (2021) [ 32 ] also reported a high prevalence of S. aureus (58.3%), Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas can be isolated from usually immunocompromised and occasionally immunocompetent individuals [ 3 ]. Antibiotic use plays a large role in developing P. aeruginosa infection in the stool [ 6 ]. There is a reported case of an elderly woman who had an episode of bloody diarrhea associated with lower abdominal pain when being treated for a urinary tract infection with antibiotics and tested positive for P. aeruginosa in stool culture.…”
Section: Discussionmentioning
confidence: 99%
“…Patients colonized with P. aeruginosa on admission tend to develop infection due to their colonizing strain during their hospital stay [4][5][6]. P. aeruginosa can cause antibiotic-associated diarrhea among immunosuppressed or hospitalized patients and children [7][8][9]. Shanghai fever caused by P. aeruginosa in children is one of the most severe enteric diseases with complications [10].…”
Section: Introductionmentioning
confidence: 99%